Geospatial assessment of climate sensitivity in Ibarapa North, Oyo State, Nigeria (2024)
This study employed remote sensing and geographic information system (GIS) to evaluate the spatial pattern of carbon(iv)oxide (CO2) concentration and the resulting climate sensitivity in Ibarapa North local government areas of Oyo State, Nigeria. The evaluation was carried out using Landsat images of 2003 and 2023, digital elevation model, as well as CO2 data collected with CO2. meter. Surface temperature and radiative forcing were generated from the satellite images using random forest algorithm in 𝑅 software environment, while the climate sensitivity was evaluated using Drakes’ Sensitivity Linear Model. The results revealed mean air temperature of 31.5oC and 32.7oC in 2003 and 2023 respectively. The area experienced positive radiative forcing mean value of about 2.69𝑊 𝑚−2, which indicates more energy being trapped on the earth’s surface that could cause warming. The climate sensitivity in 2023 was 0.4oC 𝑚−2s-2 which falls below global average of about 3oC 𝑚−2s-1. The CO2 concentration was extrapolated based on the mathematical function derived from the regression function between the variable and elevation. The results revealed positive radiative forcing and low climate sensitivity value. This may seem positive, but that doesn’t negate the need for action to mitigate adverse effects of climate change.